Antiplatelet therapy and risk of adverse cardiovascular events in peripheral artery disease. (3rd October 2022) - Kamil, S; Sehested, T S G; Blanche, P; Houlind, K; Lassen, J F; Gislason, G; Dominguez, H
Abstract: Background: Antiplatelet therapy has been shown to reduce adverse cardiovascular (CV) events in patients with PAD, but despite the well-established medication benefit, large-scale epidemiological data evaluating antiplatelet agent of choice with low bleeding risk and high antithrombotic effect is sparse. Purpose: We explored Danish healthcare registers to examine guideline-recommended antiplatelet therapy and associated risk of adverse CV outcomes in patients with PAD. Methods: All patients with a first-time diagnosis of PAD between January 1, 1997 and December 31, 2016 were identified. Patients alive six months after diagnosis were divided into four treatment groups: aspirin, clopidogrel, dual therapy (DAPT), and no antiplatelet therapy. Logistic regression models were used to estimate 1-year risk of myocardial infarction (MI), stroke, CV death, all-cause mortality, and gastrointestinal (GI) bleeding. Results: We identified a total of 85, 771 PAD patients [median age 70.6 (IQR 63–77 years), 52% male]. The results suggest that compared to no antiplatelet therapy, use of clopidogrel alone significantly decreased 1-year risk of incident MI, stroke, CV death and all-cause mortality with odds ratios 0.56 (CI 0.46–0.68), 0.69 (CI 0.59–0.81), 0.72 (CI 0.56–0.94), and 0.79 (CI 0.65–0.97) respectively. Likewise, aspirin monotherapy was associated with only a marginal reduction in 1-year risk of stroke by 11% and all-cause mortality by 7%. Odds ratios for GI bleeding were estimated to be 1.18 (CI 1.04–1.34), 1.34 (CI 0.94–1.91), and 1.54 (CI 1.05–2.26) for aspirin, clopidogrel, and DAPT groups, respectively. Conclusion: In this nationwide study, clopidogrel is associated with significantly reduced risk of MI, stroke, CV death and all-cause mortality with low risk of bleeding and appears to support clopidogrel as antiplatelet agent of choice for CV risk reduction in patients with PAD. Funding Acknowledgement: Type of funding sources: None.